Time to recovery from neonatal sepsis and its determinants among neonates admitted in Woldia comprehensive specialized hospital, Northeast Ethiopia: a retrospective cohort study - Ambaye, Kassawmar; Yimer, Ali; Mislu, Esuyawkal; Wendimagegn, Zeru; Kumsa, Henok (Frontiers in Pediatrics, 2024)
Background: Neonatal sepsis is the most serious problem in neonates. It is the leading cause of neonatal death in developing countries, particularly sub-Saharan Africa. Ethiopian 2016 Demographic Health Survey report revealed that a high number of neonatal deaths are associated with neonatal sepsis. However, limited studies are available on exposure and time to recovery inferences in Ethiopia. Therefore, this study aimed to assess the time to recovery from neonatal sepsis and its determinants among neonates admitted to Woldia Comprehensive Specialized Hospital, (WCSH), Northeast Ethiopia.Methods: A retrospective cohort study was employed to include 351 neonates using systematic random sampling at the WCSH from 7-30 March 2023. The data were entered into Epi data version 4.6 and exported to STATA 14 for analysis. Cox regression was used to identify the determinants of time to recovery from neonatal sepsis, and a variable with a p-value of less than 0.05, was used to declare significant association at a 95% confidence interval.Result: Among 351 neonates with sepsis, 276 (78.63%) recovered, and the median time to recovery was 6 days. Induced labor (AHR=0.54, 95% CI: 0.369, 0.78) and resuscitation at birth (AHR=0.7, 95% CI: 0.51, 0.974) were significantly associated with the recovery time of neonatal sepsis.The median survival time to recovery time from neonatal sepsis is comparable to previous studies results. The 25 th and 75 th percentiles were four and eight days, respectively. Health professionals working in the NICU need to pay special attention neonates born from mothers who had induced labor and resuscitated at birth.